2020
DOI: 10.1007/s11682-020-00408-1
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal connectivity in Amyotrophic Lateral Sclerosis (ALS): more than Papez circuit impairment

Abstract: Emerging evidence suggests that memory deficit in amyotrophic lateral sclerosis (ALS), a neurodegenerative disease with varying impairment of motor abilities and cognitive profile, may be independent from executive dysfunction. Our multimodal magnetic resonance imaging (MRI) approach, including resting state functional MRI (RS-fMRI), diffusion tensor imaging (DTI) and voxel-based morphometry (VBM), aimed to investigate structural and functional changes within and beyond the Papez circuit in non-demented ALS pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 75 publications
3
18
0
Order By: Relevance
“…The significant role of the hippocampus and amygdala in the discrimination between ALS and HC is also not surprising, given the multi‐systemic nature of this disorder that usually presents a variety of clinical frontotemporal manifestations as extra‐motor signatures 52–54 . As for caudate, putamen and pallidum, in our analysis both hippocampus and amygdala did not show any significant atrophy, perfusion alteration, nor a significant variation of iron content, in the analyzed ALS patients, albeit, when all these parameters were concurrently included in a multiparametric discriminative analysis, this led to a significant discrimination from HCs.…”
Section: Discussionsupporting
confidence: 48%
“…The significant role of the hippocampus and amygdala in the discrimination between ALS and HC is also not surprising, given the multi‐systemic nature of this disorder that usually presents a variety of clinical frontotemporal manifestations as extra‐motor signatures 52–54 . As for caudate, putamen and pallidum, in our analysis both hippocampus and amygdala did not show any significant atrophy, perfusion alteration, nor a significant variation of iron content, in the analyzed ALS patients, albeit, when all these parameters were concurrently included in a multiparametric discriminative analysis, this led to a significant discrimination from HCs.…”
Section: Discussionsupporting
confidence: 48%
“…The nfvPPA cohort exhibits widespread degeneration of both commissural and long association fibers with slight left hemispheric predominance in addition to thalamic and striatal projections. The C9orf72 negative ALS‐FTD cohort not only exhibits widespread WM pathology in core ALS‐associated regions such as the corticospinal tracts and corpus callosum, but in line with more recent studies, in the cerebellar peduncles, long association fibers, arcuate fasciculus, uncinate and cingulum (Bede, Chipika, et al., 2021 ; McKenna, Chipika, et al., 2021 ; Trojsi, Di Nardo, Caiazzo, et al., 2020 ) (Table 2 ). WM degeneration in ALS‐FTD patients carrying the GGGGCC hexanucleotide expansion is comparable to the anatomical patterns observed in C9orf72 ‐negative patients, but is more readily detected by FA reductions (Table 2 ).…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, a DTI study has shown that disruption of white matter integrity of the cortico-ponto-cerebellar system in ALS patients was associated with the pseudobulbar syndrome, ( Floeter et al, 2014 ). Further, cortico-ponto-cerebellar system microstructural changes have been related to memory impairment in ALS patients, ( Trojsi et al, 2020 )., Mean FA of the CPT was reduced in ALS patients in a longitudinal multicenter study ( Kalra et al, 2020 ). The CPT is associated with hand dominance-related alterations ( Kim et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%